CHILDREN'S TRANSITIONS IN EVERYDAY LIFE AND INSTITUTIONS - Nascimento, Carolina Picchetti; Pasqualini, Juliana Campregher [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2020)
The book Children's transitions in everyday life and institutions, firts published in 2019, addresses children's transitions in/between institutional practices in the light of the principles of historical-cultural psychology. Organized by Mariane Hedegaard and Marilyn Fleer, the work portrays diverse empirical situations highlighting the child's perspective in the transitional processes that, occurring from a very early age in childhood, promote the restructuring of their social relationships. This potentially holds the possibility of forming new affective-cognitive capacities. The emphasis on the child's perspective and the institutional dimension in the analysis of the leading activities are pointed out, in this review, as important contributions to Brazilian scholars of this theoretical tradition. We discuss the expansion of the scope of the concept of transition, including horizontal passages of microgenetic level, arguing for the transformation of motives and their intentional organization in educational processes to be retained as core aspects of the problem of transitions in development.
Keywords: Periods of development; Cultural-historical psychology; Transitions; Child's perspective